Fosmid-Based Physical Mapping of the Histoplasma capsulatum Genome - Magrini, Vincent; Warren, Wesley C.; Wallis, John; Goldman, William E.; Xu, Jian; Mardis, Elaine R.; McPherson, John D. (Genome Research, 2004)
A fosmid library representing 10-fold coverage of the Histoplasma capsulatum G217B genome was used to construct a restriction-based physical map. The data obtained from three restriction endonuclease fingerprints, generated from each clone using BamHI, HindIII, and PstI endonucleases, were combined and used in FPC for automatic and manual contig assembly builds. Concomitantly, a whole-genome shotgun (WGS) sequencing of paired-end reads from plasmids and fosmids were assembled with PCAP, providing a predicted genome size of up to 43.5 Mbp and 17% repetitive DNA. Fosmid paired-end sequences in the WGS assembly provide anchoring information to the physical map and result in joining of existing physical map contigs into 84 clusters containing 9551 fosmid clones. Here, we detail mapping the Histoplasma capsulatum genome comprehensively in fosmids, resulting in an efficient paradigm for de novo sequencing that uses a map-assisted whole genome shotgun approach.